Implementing virtual reality technologies to enhance digital literacy in primary education - Zulpykhar, Zhandos; Azamat, Aitgul (International Journal of Innovative Research and Scientific Studies, 2025)
Virtual reality (VR) technologies have shown promising results in the field of education. However, the number of studies directly examining the impact of VR technologies on digital literacy in primary education is limited. This study demonstrates the benefits of VR technologies and the potential of resources developed based on VR technology to support digital literacy acquisition in primary schools. The article conducted a study to examine the role of VR technologies in the development of the digital literacy of students in grades 2–4. The study involved 72 students from schools in Kazakhstan, divided into experimental and control groups. The results showed that the digital competencies of the experimental group improved compared to the control group. Students in the experimental group demonstrated improved problem-solving and information search abilities, indicating the effectiveness of using VR technologies. The results highlight the importance of implementing immersive learning technologies in primary education. These results demonstrate the potential of virtual reality to change primary education by developing basic digital skills, providing a basis for future research in this area.